More than just ripples - Baldonado, Xanthe Kaelo F.
"More Than Just Ripples" explores the story about Melu, a 25-year old artist who is commissioned to paint an underwater painting. As she seeks inspiration, Melu revisits her hometown and reminisces about her childhood, including her drowning accident years ago. Melu's journey takes a surprising turn when she rediscovers her artworks and encounters Arra and Zin, her childhood friends. Through their reconnected friendship, Melu discovers the importance of accepting change.